Women's Participation In Administration Processes In Education And Culture - Sultan Sultan; Fitriani Fitriani (Musamus Journal of Public Administration, 2019)
The purpose of this study was to determine the participation of women in the administrative process at the Office of Education and Culture in Merauke Regency. Researchers use a qualitative approach. while the data analysis technique, the authors used three stages: Condensation of data, presentation of data, and drawing conclusions from the results of this study the authors found that women's participation in the administration process went well, but there were still flaws and found other factors namely education, insight intellectual, and responsibility, Based on the results of the study showed that the factors of Coverage, Equality and partnership, Transparency, Equality and authority, Equality of responsibility and empowerment. Women's Participation in the Administration Process in the Office of Education and Culture in Merauke Regency which can be seen from these indicators has been going well the above has been going well, but in the process there are still some shortcomings, and obstacles in doing work that is still and obstacles in doing employment, namely that there are still many women who do not yet have adequate quality in carrying out and carrying out work, but these problems can be minimized to carry out the process of women's participation in administration at the Merauke Regency Education and Culture Office.